2012
DOI: 10.1097/ico.0b013e31823cbe9c
|View full text |Cite
|
Sign up to set email alerts
|

Colored Cosmetic Contact Lenses

Abstract: Over-the-counter use of decorative lenses as a cosmetic aid is rapidly increasing. Easy and unmonitored availability of these cosmetic lenses is followed by severe sight-threatening complications in young emmetropic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 17 publications
0
28
1
Order By: Relevance
“…Furthermore, four P. aeruginosa clinical isolates from human ocular surface infections (keratitis and conjunctivitis) and with varying degrees of resistance to commonly used antibiotics were included for comparison, as well as other three bacterial strains belonging to the Staphylococcus genus (i.e. S. aureus, S. epidermidis, S. hominis ) which are relevant not only for cornea, but also for conjunctival infections [44, 45]. Importantly, Esc-1a(1-21)NH 2 was found to be active against the selected clinical isolates with MIC values measured in the range of 2–8 μM for P. aeruginosa strains compared with a MIC of 1 μM or 8 μM for S. hominis or S. epidermidis , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, four P. aeruginosa clinical isolates from human ocular surface infections (keratitis and conjunctivitis) and with varying degrees of resistance to commonly used antibiotics were included for comparison, as well as other three bacterial strains belonging to the Staphylococcus genus (i.e. S. aureus, S. epidermidis, S. hominis ) which are relevant not only for cornea, but also for conjunctival infections [44, 45]. Importantly, Esc-1a(1-21)NH 2 was found to be active against the selected clinical isolates with MIC values measured in the range of 2–8 μM for P. aeruginosa strains compared with a MIC of 1 μM or 8 μM for S. hominis or S. epidermidis , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Risk-taking and noncompliant behavior were also noted by the authors. More recently, Singh et al reported 13 cases of complications in patients wearing cosmetically tinted contact lenses 8. Much like the cases reported by Steinemann et al, none of the patients were aware of or instructed about proper lens handling techniques prior to use, and poor compliance was a common factor in all cases.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the popularity of cosmetically tinted lenses, there have been negative reports regarding safety in the literature 5–10. Compliance-related reports in the literature all have in common patient histories of receiving the contact lenses without a prescription, with no or limited care, limited handling and wearing instructions, and no follow-up examinations 6,810. Complications related to compliance are not limited to cosmetically tinted contact lenses.…”
Section: Discussionmentioning
confidence: 99%
“…ese lens materials are composed of copolymers of HEMA and other hydrophilic or lipophilic monomers such as Nvinyl pyrrolidone (NVP) and methacrylates, the diversity of which contributes to the wide range of water contents of both ionic and nonionic lens materials [1,2]. Among these contact lenses, cosmetic-type soft lenses containing colored patterns are rapidly gaining market share over the conventional clear-type soft lenses among young people, especially in Asian markets [3,4]. Cosmetic contact lenses are used to change or enhance the iris color to give a softer look through complex print patterns or a pigmented ring pattern that overlap with the limbal ring of the iris [5].…”
Section: Introductionmentioning
confidence: 99%